Effects of planting distance and depth on PTO load spectrum of a small riding-type transplanter - Kim, Wan-Soo; Kim, Yeon-Soo; Kim, Taek-Jin; Nam, Kyu-Chul; Kim, Tae-Bum; Han, Tae-Ho; Im, Ryu-Gap; Kim, Yong-Hyeon; Kim, Yong-Joo (International Journal of Agricultural and Biological Engineering, 2020)
The aim of this study was to analyze the effects of the planting distance and depth on the power take-off (PTO) load spectrum of a small riding-type transplanter for the optimal design of the transplanter. To measure load data during actual planting operation, a load measurement system was developed using a torque sensor, a data acquisition system, and an inverter. Field experiments were conducted at four planting distances (26 cm, 35 cm, 43 cm, and 80 cm) and three planting depths (85 mm, 105 mm, and 136 mm) in a field with similar soil conditions. The measured load data were inverted into a load spectrum using rain-flow counting and Smith-Watson-Topper (SWT) methods. The safety factor of a transplanter according to the planting conditions was analyzed using the converted load spectrum and commercial software. The load spectrum for all planting conditions showed torque ratios similar within a high cycle region of 108 to 109. The torque ratio increased when the planting depth increased and planting distance decreased in the low cycle region under less than 108 cycles. The safety factors of the PTO driving gear and the driven gear increased as the planting distance increased at all planting depths. When the planting depth decreased at the same planting distance, the safety factor of the PTO gears increased. The results of this study might provide useful information for a transplanter PTO design considering the working load according to the various planting conditions. Keywords: transplanter, planting distance, planting depth, power take-off, load spectrum, safety factor DOI: 10.25165/j.ijabe.20201302.4187 Citation: Kim W-S, Kim Y-S, Kim T-J, Nam K-C, Kim T-B, Han T-H, et al. Effects of planting distance and depth on PTO load spectrum of a small riding-type transplanter. Int J Agric & Biol Eng, 2020; 13(2): 57–63.